Penyuluhan Perencanaan Pembelajaran Bermakna dan Menyenangkan dalam Kurikulum Merdeka - Citrowati, Endang; Syofrianisda, Syofrianisda; Hanifah, Nisaaul; Putri, Rika Rahmi; Wati, Wati (Universitas Syiah Kuala, 2025)
This Community Service Program (PKM) aims to motivate teachers to plan meaningful and enjoyable learning for early childhood. Meaningful and enjoyable learning in the Independent Curriculum for early childhood (PAUD) emphasizes relevant, engaging, and child-centered learning experiences. Therefore, outreach efforts are achieved through learning tailored to individual needs, involving exploration, play, and social interaction, and creating a positive and supportive learning environment that teachers can implement. This is one learning model that can be implemented in the Independent Curriculum. This approach integrates deep teaching in early childhood. The methods used in this community service are 1) Needs Mapping, 2) Education, and 3) Evaluation. By implementing a medley, joyful, and level-full approach, children's insights can be broadened through learning activities.